Análise da Sustentabilidade Ambiental em Estabelecimentos Agrícolas em Goiás - ALVES, Luiz Batista (2010)
In this work are presented and discussed other forms of studies related to analysis of environmental sustainability with the use of methods that permit the human environment to demonstrate its environmental impacts on rural properties in the town of Silvânia, State of Goiás. The choice of the municipality of Silvânia occurred because of present permanent preservation areas susceptible to exploitation by various activities in the city, allowing checking the environmental sustainability in land reform settlements in comparison with other rural property. The Project for Sustainable Development (PDS), established in 1999 comes meet the new brazilian environmental laws, seeking the durability and perpetuity of the settlements (family farm) in order to provide less environmental impact. On the other hand, has been observed that in large farms (agricultural employer) occurs deforestation to expand the area explored, giving rise to a particular crop, in seeking increases in production. Studies have shown the link between deforestation and biodiversity conservation consequences that hinder sustainable development. Still, the methodology of the indices applied to the settlement of São Sebastião da Garganta and João de Deus, the results showed considerable levels of sustainability. Analyzing the settlements in comparison with the Farm Silvânia through satellite images, it appears that the agrarian reform, there were minor differences of deforestation between periods and a greater difference occurred in the Farm Silvânia as favoring extensive livestock farming. But we can not say that the settlements have a higher level of environmental sustainability, where by means of observation of annual averages, there are almost identical proportions of deforestation, and that the settlements, deforestation occurred in a more fragmented than in Farm Silvânia and may cause a greater reduction of species in the environment, reducing the potential for environmental sustainability. Finally, the results may serve as guidance in formulating environmental policy to keep families in agrarian reform settlements, contributing to sustainable development of rural properties in the region, coupled with supervision to allow continuity in the production process in a sustainable manner.